Crime scenes and mystery players! Using driving questions to support the development of statistical literacy. (4th December 2015) - Leavy, Aisling; Hourigan, Mairead
Abstract: We argue that the development of statistical literacy is greatly supported by engaging students in carrying out statistical investigations. We describe the use of driving questions and interesting contexts to motivate two statistical investigations. The PPDAC cycle is use as an organizing framework to support the process statistical investigation.